2009
DOI: 10.1097/aln.0b013e3181bdf857
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Ameliorates Gas Exchange and Attenuates Lung Damage in Experimental Lipopolysaccharide-induced Lung Injury

Abstract: Postconditioning with sevoflurane attenuates lung damage and preserves lung function in an in vivo model of acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 54 publications
6
88
1
5
Order By: Relevance
“…In a 2009 study, Voigtsberger et al 12 observed improved oxygenation and attenuated inflammatory response in an LPS-induced ALI rat model after 6 hours when sevoflurane was used rather than propofol. Ferrando et al 28 endorsed the results of Voigtsberger et al 12 in a porcine 2-hit ARDS model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2009 study, Voigtsberger et al 12 observed improved oxygenation and attenuated inflammatory response in an LPS-induced ALI rat model after 6 hours when sevoflurane was used rather than propofol. Ferrando et al 28 endorsed the results of Voigtsberger et al 12 in a porcine 2-hit ARDS model.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2009 study, Voigtsberger et al 12 observed improved oxygenation and attenuated inflammatory response in an LPS-induced ALI rat model after 6 hours when sevoflurane was used rather than propofol. Ferrando et al 28 endorsed the results of Voigtsberger et al 12 in a porcine 2-hit ARDS model. In addition, the anti-inflammatory effects of volatile anesthetics in the deflated-reventilated lung undergoing hypoxia-reoxygenation could also be verified in clinical investigations: De Conno et al 29 found that sevoflurane reduced pulmonary inflammatory response and chemoattraction of neutrophils in patients undergoing 1-lung ventilation for lung resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with controls under propofol anesthesia, inhaled anesthetics result in attenuation of cytokine elevations in both the ventilated and the operative lung [ 41 ]. This approach appears to translate into better outcomes, as patients in the sevofl urane arm experienced less composite adverse events [ 42 ]. Pressure-supported ventilation with PEEP is more likely to maintain optimal lung volumes during emergence.…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…For example, Suter et al have recently shown that, in an in vitro model of endotoxin-induced lung injury, production of inflammatory proteins is attenuated in alveolar epithelial cells following sevoflurane preconditioning (30). Post-conditioning with sevoflurane attenuates lung damage and preserves lung function in in vivo and in vitro models of acute respiratory distress syndrome (ARDS) (29,32). Additionally, Conno et al showed that patients who received sevoflurane while undergoing one-lung ventilation for thoracic surgery experienced a significant reduction in inflammatory mediators and significantly better clinical outcomes than patients who received propofol (2).…”
mentioning
confidence: 99%